Improving the Elementary Science Program. - Frazier, Alexander (Educational Leadership, 1962)
The article presents information on the need to improve the elementary science program. School systems in Ohio have been and now are expanding large amounts of teachers and supervisory energy and considerable sums of money to upgrade science teaching in the elementary school. Science is a field in which what is worth teaching, how it should be learned, and how much time it should be given are still open questions that have to be worked through with many teachers. As compared with most fields, science is relatively new in the elementary school. Science is a field in which the preparation of elementary teachers varies greatly. The emphasis in many programs of elementary science has been on the descriptive or has dealt largely with collecting, identifying and classifying objects or items found in the immediate environment. Culturally, science has been regarded as a man's field, yet most elementary teachers are women. Teachers need to come to grips with the importance of science in the elementary program. Many teachers need to know more science in terms both of its scope and its process if they are to teach more of it or to teach it more confidently and effectively.